PENGARUH EFEKTIFITAS TERAPI BERMAIN FLASHCARD TERHADAP INTERAKSI SOSIAL PADA ANAK AUTIS DI SLB NAZARETH MANADO - Mangawuhi, Delindra (Journal Of Community & Emergency, 2024)
Several problems are often encountered in pre-school age children, namely not being able to speak clearly, relatively little vocabulary mastery, slurred speech (article errors when pronouncing letters), difficulty understanding commands, barriers to socialization and being less active. The causative factors that affect the development of children are divided into intrinsic factors (from the child's self) and extrinsic factors (from the environment). There are still many cases of autism in the world, based on the World Health Organization (WHO) in 2017 in the world it is estimated that 1 in 160 children suffer from autism. Currently in Indonesia there is no statistical data on the number of people with autism. However, individuals with autism are thought to have increased. This can be seen from the number of visits to general hospitals, mental hospitals at child development clinics which are quite significant from year to year. This research is a pre-experimental research without a control group (one group pretest-post test design). This type of research is a quantitative research time in January 2022 and the research location is at the Extraordinary School, Tuminting Village. The statistical test used is the statistical test "paired t-test" with a 95% confidence degree if < 0.05 The results obtained that the P value = 0.000 while the value of = 0.05 so that the results of the paired samples test t value of sig. (2-tailed) tailed is 0.000 < 0.05, then Ho is rejected and Ha is accepted which means that there is an average difference between the pretest and posttest, which means that there is an effect of the effectiveness of Flashcard play therapy on social interactions in autistic children at SLB Nasareth Tuminting Manado City of Manado. Conclusion From the results of the research The results of research on social interaction in autistic children before giving Flashcard play therapy at SLB Nasareth Tuminting Manado were more or less good. Most of the social services in autistic children before giving Flashcard play therapy at SLB Nasareth Tuminting Manado. Suggestions in this study are that this research is expected to be input for school administrators that this flashcard game is very useful for students with the aim of improving their abilities and training children in communicating, speaking/imitating, recognizing letters and numbers and can improve eye contact.